Efficacy and safety of dupilumab in atopic dermatitis in elderly patients: a retrospective study. (24th May 2020) - Napolitano, M.; Fabbrocini, G.; Scalvenzi, M.; Blasio, C.; Stingeni, L.; Patruno, C.
Summary: Atopic dermatitis (AD) is a common inflammatory skin disease with high prevalence in both children (15–30%) and adults (2–10%), but limited data are available for older people. Elderly patients form a challenging group, as multiple comorbidities, associated polypharmacy and failures with previous treatments are common. We performed a retrospective observational study on elderly (≥ 65 years) patients treated with dupilumab, monoclonal antibody to the shared alpha subunit of the interleukin‐4 and ‐13 receptor approved for the treatment of moderate‐to‐severe AD in adults.